Influencing Side-Effects to Medicinal Treatments: A Systematic Review of Brief Psychological Interventions - Webster, Rebecca K.; Rubin, G. James (Frontiers in Psychiatry, 2019)
Background: Nocebo effects contribute to a large proportion of the nonspecific side-effects attributed to medications and are mainly generated through negative expectations. Previous reviews show that interventions designed to change participants’ expectations have a small effect on pain experience. They are also effective in reducing side-effects caused by exposure to sham medications. To date, there has been no review of the influence of such interventions on symptoms attributed to real medicinal treatments. Objective: To review studies using a randomised controlled design testing the effect of brief psychological interventions compared to usual practice on the side-effect experience to medicinal treatments in healthy volunteers and patients. Methods: We searched Web of Science, Scopus, Medline, PsycINFO, PsycARTICLES, and Cohrane CENTRAL using search terms for randomised controlled trials along with ‘nocebo,’ ‘placebo effect,’ ‘medication,’ ‘side-effects’ and associated terms. Studies were eligible if they studied a human population, used an active medicine, delivered a brief psychological intervention intended to reduce side-effect reporting compared to usual care or no intervention, and used a randomised controlled design. Because of the heterogeneity of the literature we used a narrative synthesis and assessed evidence quality using the GRADE approach. Results: Our database search and supplementary search of the reference sections of included studies retrieved 50,140 citations. After screening, full text review and manual reference searches, 27 studies were included. The quality of the studies and evidence was judged to be low. The strongest and most consistent effect came from omitting side-effect information, although surprisingly de-emphasising side-effects did not affect side-effect reporting. Other techniques, including priming, distraction, and altering the perception of branding, produced mixed results. Conclusion: Brief psychological interventions can influence side-effect reporting to active medications. Research is currently investigating new ways to de-emphasise side-effects whilst still upholding informed consent, but larger confirmatory trials with suitable control groups are needed. The literature in this area would be improved by more detailed reporting for studies.